Design and production of shaft angle position detector system using ATMEGA 8535 - FAJAR (NIM 13103080), LUCKY
Many kind of production machineries belongs to rotational type, such as pump, blower, compressor, and turbine. The main vibrational source of these machineries is the unbalanced rotor that was caused by the existence of unbalance mass on it’s rotational components. To solve this kind of problem, balancing process is needed. Angle detection has become an important part in balancing process. Therefore, a better accuracy for angle detection tools need to be developed. On this final assignment, a shaft angle potition detector system that not depending on the shaft diameter is designed. This research was done so the result of angle potition measurement with encoder as an angle sensor and also a key phasor as a zero reference, can be seen automatically using a signal processing unit. Signal processing unit that was developed in this final assignment is designed with 3 input source. In this unit the 0 input is connected to key phasor and the 1 and 2 input is connected to encoder angle position sensor. With those 3 input, the signal processing unit can be used for detecting position of shaft angle. Beside that this signal processing unit can be used for detecting rotational direction of angle and rotational speed (rpm). From the experiment result, this signal processing unit for detection position of shaft angle, show relatively same result with MSA HP 353650, with miximum range is 6,47 % and minimum range 0,97 %. Meanwhile from the experiment result for rotational speed has maximum range 7,2 % and maximum range 3,59 %.